Efficacy of Micronutrient Supplementation from Local Food of Bada Fish (Stolephorus Insularis) on the Status of Anemia Among Adolescents in Padang City - ., Safyanti; ., Andrafikar (KnE Life Sciences, 2019)
The objective of this study was to determine the effectiveness of functional supplementary food formulas of the bada fish flour against the levels of adolescent Hb in the city of Padang, West Sumatra Province. This research is a continuation of the previous research – preparing additional food products for anemia (FUMIA) based on local food ingredients of bada fish in the form of cookies. The research design used was the One Group Free Post T by conducting an efficacy test on the FUMIA formula intervention with a duration of intervention of 21 days. The results showed an increase in the average Hb level of the subjects before being given an intervention of 0.35 mg%, but not significantly different. For further research, it is necessary to increase the number of subjects/research samples and the implementation of longer interventions and the provision of interventions accompanied by the provision of foods containing high vitamin C so that iron absorption is better.